Effect Of Classical Music And Progressive Muscle Relaxation On Anxiety Levels In Laboring Mothers - Qonitun, Umu; Munir, Miftahul (Chakra Brahmanda Lentera Institute, 2025)
Background: Anxiety is a feeling that is most commonly experienced by pregnant women when approaching childbirth; what's more, childbirth is already known to require a cesarean surgery. Anxiety during pregnancy can harm the mother and fetus, such as increasing the risk of premature birth, impaired fetal development, and psychological disorders in the mother. The purpose of this study was to determine the effect of classical music therapy and progressive muscle relaxation on anxiety levels in pre-section cesarean patients in the delivery room of Tuban Hospital.. Methods: This study employed a pretest-posttest quasi-experimental design. The sample consisted of 44 pre-section cesarean patients from two hospitals in Tuban Regency in January and February 2024, selected using simple random sampling. Respondents were divided into two groups: classical music therapy (n = 22) and progressive muscle relaxation (n = 20). Anxiety level was measured with HARS and analysed using the Wilcoxon test. This study underwent ethical review by the Health Research Ethics Institute of IIK NU Tuban. Results: The results showed that classical music therapy and progressive muscle relaxation effectively reduce anxiety in pre-section cesarean delivery mothers. The Wilcoxon test in both groups showed a value of ρ <0.001 (<0.05), indicating a significant effect on reducing anxiety levels at Tuban Regency Hospital. Conclusion: Both interventions proved to be significantly effective in reducing anxiety. Based on the results of this study, classical music therapy and progressive muscle relaxation are expected to be non-pharmacological alternatives to reduce anxiety levels in pre-section cesarean patients.